Compositional MRI techniques for evaluation of cartilage degeneration in osteoarthritis. Issue 10 (October 2015) - Guermazi, A.; Alizai, H.; Crema, M.D.; Trattnig, S.; Regatte, R.R.; Roemer, F.W.
Summary: Osteoarthritis (OA), a leading cause of disability, affects 27 million people in the United States and its prevalence is rising along with the rise in obesity. So far, biomechanical or behavioral interventions as well as attempts to develop disease-modifying OA drugs have been unsuccessful. This may be partly due to antiquated imaging outcome measures such as radiography, which are still endorsed by regulatory agencies such as the United States Food and Drug Administration (FDA) for use in clinical trials. Morphological magnetic resonance imaging (MRI) allows unparalleled multi-feature assessment of the OA joint. Furthermore, advanced MRI techniques also enable evaluation of the biochemical or ultrastructural composition of articular cartilage relevant to OA research. These compositional MRI techniques have the potential to supplement clinical MRI sequences in identifying cartilage degeneration at an earlier stage than is possible today using morphologic sequences only. The purpose of this narrative review is to describe compositional MRI techniques for cartilage evaluation, which include T2 mapping, T2* Mapping, T1 rho, dGEMRIC, gagCEST, sodium imaging and diffusion weighted imaging (DWI). We also reviewed relevant clinical studies that have utilized these techniques for the study of OA. The different techniques are complementary. Some focus on isotropy or the collagen network (e.g., T2 mapping) and others are more specific in regard to tissue composition, e.g., gagCEST or dGEMRIC that convey information on the GAG concentration. The application and feasibility of these techniques is also discussed, as they will play an important role in implementation in larger clinical trials and eventually clinical practice.